Analisis Preferensi Konsumen Dalam Menentukan Strategi Pemasaran Produk Tempe di Kabupaten Tana Toraja, Sulawesi Selatan - Aguinalty Sofia Rante Allo; La Sumange; Syamsinar Syamsinar; Helda Ibrahim (Jurnal MeA (Media Agribisnis), 2026)
. In Lapandan Village, Makale District, tempeh entrepreneurs such as Jeslyn Tempeh Business face various challenges in maintaining and developing their business amidst increasingly dynamic changes in consumer preferences. One of the main problems faced is the lack of a structured marketing strategy based on consumer data, so that the tempeh products offered are less attractive to the wider market. In addition, product promotion is still carried out conventionally through limited distribution channels without the use of digital media and without paying attention to the characteristics of the target market segment. The type of research used SWOT analysis in this study is used to identify internal and external factors that influence the development of the tempeh business, as a basis for developing a strategy based on consumer preferences. The results of the study Based on the SWOT analysis, the IFAS value of 3.56 and EFAS of 3.36 places Jeslyn Tempeh Business in Quadrant I (SO-Aggressive Strategy), which means it has high strengths and opportunities. The most appropriate strategy is to utilize internal strengths to capture external opportunities, through product innovation, digital promotions, expansion of distribution networks, and partnerships with local business actors. The SO strategy is the primary choice for increasing business growth and competitiveness, as it strengthens Tempe Jeslyn's market position and supports the sustainable development of local food